Gaining Effective Profitability with Training in Factory Overhead Cost Calculation for Printing Businesses - Yenny Wati; Yusrizal Yusrizal; Mimelientesa Irman; Fadrul Fadrul; Nicholas Renaldo (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2024)
Inadequate information and the ineffective ability to distribute factory overhead costs to determine production costs might lead to lower-than-optimal earnings. This problem is the basis for this PKM action because the business owner's intended strategy is ineffective. This PKM activity wants to assist and boost efficiency in obtaining profits for printing entrepreneurs by developing knowledge and capacity to accurately calculate the cost of production, particularly factory overhead costs, to estimate a business's profit or loss each period. The approaches used in this PKM action include empowerment, instruction, and practice. On Saturday, September 7, 2024, the owner of a printing business and three of his employees participated in PKM offline. In line with evaluation findings, instruction, and practice boosted competency by 75%. This improved ability is the outcome of mistakes being identified through offline instruction and the PKM team suggesting fixing any difficulties that exist. This PKM action can maximize the annual profit gained for the printing business's long-term viability. This PKM was held so that the printing business may develop, improve, and actively contribute more to Indonesia's economic growth.Pengetahuan yang minim dan kemampuan mengalokasikan biaya overhead pabrik yang tidak efektif dalam menentukan harga pokok produksi dapat mengakibatkan laba yang diperoleh kurang optimal. Permasalahan tersebut menjadi dasar dilakukan kegiatan PKM ini karena strategi bisnis yang direncanakan oleh pemilik usaha menjadi tidak tepat. Kegiatan PKM ini bertujuan untuk membantu dan meningkatkan efisiensi dalam pencapaian laba bagi pelaku usaha percetakan dengan meningkatkan pengetahuan dan kemampuan dalam menentukan biaya produksi khususnya biaya overhead pabrik secara akurat untuk mengetahui besarnya laba maupun rugi suatu bisnis setiap periodenya. Metode dalam kegiatan PKM ini adalah pemberdayaan, pelatihan, dan praktik. Pelaku usaha percetakan dan tiga orang pegawainya mengikuti PKM secara luring pada Sabtu, 7 September 2024. Bersumber pada data evaluasi, setelah latihan dan praktik, kemahiran berkembang sebesar 75%. Kemahiran yang meningkat tersebut disebabkan kekeliruan bisa diketahui dalam pelatihan secara luring dan tim PKM menyampaikan rekomendasi untuk membenahi kekeliruan yang terjadi. Kegiatan PKM ini bisa mengoptimalkan pendapatan laba yang diperoleh setiap tahun berjalan untuk kelangsungan usaha percetakan. PKM ini diadakan agar usaha percetakan dapat berkembang, meningkat, dan berperan aktif dalam pertumbuhan perekonomian Indonesia.